The effects of layered curriculum on students' academic achievement and attitudes in social studies course - Gömleksiz, Mehmet Nuri; Öner, Ümmühan (My University, 2013)
The aim of this study is to compare the effects of layered curriculum and traditional teacher centered teaching method on students' academic achievement in Social Studies course and their attitudes towards the course. Study group included forty-nine sixth graders enrolled at Bahçelievler Elementary School in Elazig city center in 2009-2010 academic year. Both quantitative and qualitative research designs were used in the study. A pretest-posttest control group experimental design was employed in quantitative part of the study. The students were randomly assigned into two groups; an experimental group and a control group. Experimental group used layered curriculum as an instruction method while control group used traditional teacher-centered instruction. An achievement test including 40 questions and an attitude scale developed by Emir (2001) were used to collect quantitative data while an interview form was used to collect qualitative data. Mean score of the test was measured to be 0,54, KR-20 value was calculated to be 0,82. The results revealed that experimental students who used layered curriculum were more successful than the controlled students who used traditional teacher centered instruction. The attitude scale results showed that layered curriculum had a significant positive effect on students' attitudes towards Social Studies course. In qualitative part of the study, five sub themes were determined related to the implementation of layered curriculum. Based on the study results, it is recommended that layered curriculum should be used at different grade levels and different courses.
Basamakli ö?retim programinin sosyal bilgiler dersinde ö?rencilerin akademik başarilarina ve tutumlarina etkisi
Keywords: Attitude; Layered curriculum; Social Studies course; Teacher-centered instruction